Analisis Perbandingan Penerapan Metode MOORA dan SAW dalam Kelayakan Pemberian Bantuan Uang Kuliah Tunggal - Rima Tamara Aldisa; Ade Priyatna; Fatiyah Saidah; Kasta Yudha Siahaan; Mesran Mesran (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Single Tuition Fee (UKT) is a tuition payment rule that funds each student according to his economy, especially at PTN whose tuition fees are also determined from the student's economy. Students pay for the semester which is decided according to the single tuition fee minus the costs borne by the government, in other words each student only pays one component. At Budi Darma University, the payment of the Single Tuition Fee (UKT) has been determined by the campus by being able to pay in 6 installments per year in order to ease the payment of tuition fees to students. However, the number of students who meet the requirements in applying for UKT assistance makes it difficult for the campus in the selection process. Therefore, a decision support system is needed to solve a problem by applying the comparison of the Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) and Simple Additive Weighting (SAW) by including weighting with the Rank Order Centroid (ROC) method to get accurate and effective results. From the test results, getting the best alternative that is considered worthy of single tuition assistance is in the same alternative, namely A7 on behalf of Zaza Mutiara Arini. Calculations using the MOORA method get the best preference value of 0.7391 while calculations using the SAW method get the best preference value of 0.8976.